Development of Problem-based Learning-Based E-Module Assisted by QR Code Measurement Materials for Grade IV Elementary School Students - Isnanda, Adela Aprilia; Mas'ula, Siti; Yuniawatika , Yuniawatika (Journal of Education for Sustainability and Diversity, 2025)
This research is a development research with the aim of using QR codes to develop problem-based learning e-modules for measurement materials in grade 4 elementary school students. This study uses the ADDIE model with the stages of analysis, design, development, peaking, and evaluation. Data collection techniques are carried out by interviews, questionnaire distribution, and tests. The data analysis techniques in this study used normality tests, homogeneity tests, and t-tests. The results of the validation test by experts gave an average result of 97.60% and were classified as very valid. The results of the product practicality test obtained an average score of 95.44% and were classified as very practical. The results of the product effectiveness test showed a significant value of 0.000 < 0.05. Based on the results obtained, it can be concluded that the e-module teaching materials for broad measurement materials are very valid, practical and effective to be used in the mathematics learning process.